Role of T cell—glial cell interactions in creating and amplifying central nervous system inflammation and multiple sclerosis disease symptoms - Huseby, Eric S.; Kamimura, Daisuke; Arima, Yasunobu; Parello, Caitlin S.; Sasaki, Katsuhiro; Murakami, Masaaki (Frontiers in Cellular Neuroscience, 2015)
Multiple Sclerosis (MS) is an inflammatory disease of the Central Nervous System (CNS) that causes the demyelination of nerve cells and destroys oligodendrocytes, neurons and axons. Historically, MS has been thought of as a T cell-mediated autoimmune disease of CNS white matter. However, recent studies have identified gray matter lesions in MS patients, suggesting that CNS antigens other than myelin proteins may be involved during the MS disease process. We have recently found that T cells targeting astrocyte-specific antigens can drive unique aspects of inflammatory CNS autoimmunity, including the targeting of gray matter and white matter of the brain and inducing heterogeneous clinical disease courses. In addition to being a target of T cells, astrocytes play a critical role in propagating the inflammatory response within the CNS through cytokine induced NF-ΚB signaling. Here, we will discuss the pathophysiology of CNS inflammation mediated by T cell – glial cell interactions and its contributions to CNS autoimmunity.